CRIME`S EFFECTS ON THE DEVELOPMENT OF SOCIETY AND ECONOMY - Rajab Hussain; Dr. Roohi Ahmad (International Journal of Contemporary Issues in Social Sciences, 2024)
All societies, no matter how advanced, have experienced violence at some point. That exists before humans. It is alarming that most communities, particularly those in developing nations, allow criminals to escape punishment for their crimes. Victims of crime endure a tremendous deal of pain and fear. In addition to lowering transaction costs, discouraging investment, and eventually serving as a catalyst for migration, crime frequently impedes society’s ability to advance socioeconomically and adds to global economic inequality. With the goal of supplying governments with information to enable them to strictly regulate all criminal activity within their borders and foster better societies, this research attempts to examine the global expressions of crime. Reviewing scholarly articles from reports and journals served as the foundation for the approach methodology. The methodology of qualitative analysis was employed to gather secondary data from published and unpublished works. The major findings showed evidence of a wide range of criminal activity, including banditry, kidnapping, rape, theft, and murder. Crime thus encourages corruption and obstructs the advancement of any society. Ultimately, crime affects people at all levels and is not influenced by personal boundaries or traits. Inaction on the part of governments to support the global fight against terrorists, criminals, and bandits will mean that this depressing activity will persist as a major contributing factor to the lack of socio-economic development.